MORPHOLOGY OF NON-VENTILATED TRANSPLANTED RAT LUNGS - Dušek, Jaroslav; Kolář, František; Korecký, Bořivoj (Biomedical papers, 1998)
Morphological changes in lung tissue of heterotopic heart-lung transplants have been studied 28 days following transplantationin 20 rats. Lung tissue showed disperse haemorrhagic necrosis often sparing bronchi and branches of pulmonaryartery and conspicuous accumulation of bronchial secretion. Partial disappearance of cardiac muscle cells from the wallsof pulmonary veins has been ascribed to tissue hypoxia.
Keywords: R at / Experimental / Heterotopic / Lung transplant / Morphology / Bronchopulmonary sequestration